2010
DOI: 10.7773/cm.v37i4b.1769
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influence on the variation of the reproductive cycle of Trisopterus luscus (Gadidae)

Abstract: It is well documented and accepted that the reproductive potential of a population is not only influenced by the abundance of spawners but also by their age, size, and condition. Most studies of maternal effects on the reproductive potential have focused on factors such as egg production and quality, and less attention has been paid to the maternal influence on the temporal variation of the reproductive cycle. The present study introduces and describes some possible sources of variation in the reproductive cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…To assess the average length for each spawning period, logistic regression models were constructed for each species using the proportion of spawning capable females (actively spawning sub‐phase included) against the total number of mature females per week (in a calendar year), and developing the models when >50% of the females were in spawning condition in two separate periods to describe the onset and the end of the spawning season. In this way, the extent of the spawning season for each species was estimated from the dates over which 50% of females would be spawning capable between the onset and end of the spawning season (Alonso‐Fernández & Saborido‐Rey, ; Lowerre‐Barbieri et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…To assess the average length for each spawning period, logistic regression models were constructed for each species using the proportion of spawning capable females (actively spawning sub‐phase included) against the total number of mature females per week (in a calendar year), and developing the models when >50% of the females were in spawning condition in two separate periods to describe the onset and the end of the spawning season. In this way, the extent of the spawning season for each species was estimated from the dates over which 50% of females would be spawning capable between the onset and end of the spawning season (Alonso‐Fernández & Saborido‐Rey, ; Lowerre‐Barbieri et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…It was observed that lipids play an important role as stored energy that can affect fecundity, oocyte quality, and larval viability (Wiegand, 1996;Lambert et al, 2003;Aristizabal, 2007). Therefore, because the liver is generally the organ with the highest levels of lipid storage for gadoids, the HSI may be considered a good descriptor of female condition, and a strong infl uence on reproduction (Marshall et al, 1999;Marteinsdottir and Begg, 2002;Alonso-Fernández, 2011).…”
Section: Maternal Effects On Fecundity and Egg Quality Of The Patagonmentioning
confidence: 99%
“…Comparison of this variable between both length The hepatosomatic index was the maternal condition measure that best correlated with fecundity in Argentine Hake in this study. Different authors have reported that the liver is the main deposit of lipids for gadoids and have considered this organ as the main source of energy for reproduction (Lambert and Dutil, 1997;Alonso-Fernández, 2011). In addition, certain egg constituents, such as yolk proteins and egg coat substances, are synthesized in the liver (Brooks et al, 1997).…”
Section: Figurementioning
confidence: 99%
“…This storage dynamic seems to be in accordance with the relative short spawning period indicated both by histological observations and I G , and the high degree of synchronization among individual spawning periods (81% of the females were spawning in April-May). Strong seasonality is typical of capital breeders, and although seasonality is common in cold-water habitats with restricted spawning seasons (Lowerre-Barbieri et al, 2011b), it has been reported also for temperate species with an intermediate strategy (Alonso-Fernández & Saborido-Rey, 2011;2012;Alonso-Fernández et al, 2014). Nevertheless, additional effort is required to properly investigate the energy allocation strategy with biochemical data to better understand the relation between energy reserves and reproduction in D. dentex.…”
Section: Reproductive Strategymentioning
confidence: 99%